Monitoring System for Compression Sleeves - Joaquim Tiago Oliveira Cardoso (2017)
Lymphedema is correlated with cancer treatment. During the treatment, lymphatic nodes can be removed or radiated, that can stop the normal flow of lymph resulting in the build up of lymph. As soon detection occurs more easy is to treat Lymphedema and to assess it is measure the perimeter of affected and unaffected arm in three zones. The compression sleeve is used in the lymphedema treatment, sewing to it a model made by conductive thread is possible measure impedance. Therefore the impedance is correlated with force aplied in sleeve, monitoring this way the increase/decrease of lymphedema.